2d Deep Cavity Flow, Lid Driven Using Conventional Methodwith New Perspective - Muhammad Saifuddin, Idris; N. M. M., Ammar (2010)

(untitled)
In this study, conventional FDM with new perspective is applied for simulation of lid- driven flow in a 2-D, rectangular, deep cavity. The code for deep cavity is presented using rectangular cavity 100 x 300, 100 x 200 and 100 x100 with depth ratio of 3,2 and 1 respectively. Results are presented in streamlines pattern for deep cavity flow at steady state for Reynolds numbers of 100, 400 and 1000. Several features of the flow, such as the streamlines pattern, contour of stream function and midsection velocity profile are investigated. Result for deep cavities under steady state shows that the vortex pattern at the bottom enlarge, which thencombine to form a second primary-eddy as the cavity depth-ratio is increased. As the Reynolds number increase, the form of primary vortex and the second primary-vortex then formed through afast transition of an unsteady wall-eddy. Midsection velocity also yields high as Reynolds number increase. The predicted result from FDM with new perspective gives more improvement results as grid mesh increases.